Evaluation Of The Implementation,Use And Effect Of A Computerized Management Information System In College Of Business Universiti Utara Malaysia - Mostafa, Mousa Rahil (2008)
Using the theory acceptance model as its basis, this study is to identify the relationships among perceived usefulness, perceived ease of use and computerized implementation. Furthermore, for body of knowledge, this study will present the clear description of information technology implementation such as internet among university staff, lecturer and students. The significance of this research also to apply the TAM in the context of computerized acceptance to the management information system in college of business. This study proposes the usefulness and ease of use as the construct to enhance the understanding of an individual's acceptance behavior of ICT in COB of UUM context. Technology acceptance model plays an important role in the computerized management information system.